Natural Tourism Landscapes on The Slope of Merbabu - Muhamad, Muhamad; Ahmad, A B (International Journal of Architecture and Urbanism, 2025)
The natural tourism landscape in the utilization zone on the slope of Merbabu has experienced significant development in the utilization of the area's footprint in the form of an area utilization permit as a site design. The slope of the Merbabu area is an area that provides environmental services and natural tourism. This study examines using business and public spaces as a community interaction to exploit nature tourism. The study method developed is a combined qualitative and quantitative approach (mixed methods) which are descriptive qualitative, and quantitative; combined analysis (mixed methods) is an analysis of data collection using tests, questionnaires, and triangulation (combined). The results showed community interaction in the use of business and public space, especially in the utilization zone of the Merbabu slope area. In conclusion, the form of business and public space has the characteristics of alternative tourism.